ANALYSIS OF THE STATUS AND PROSPECTS OF DEVELOPMENT OF THE BELARUSIAN ECONOMY ON THE RAIL TRACK - Matvietsov, V. I.; Kovtun, P. V.; Kiebikov, O. O. (Science and Transport Progress, 2003)
The analysis of the current condition of the Byelorussian railway facilities is given and prospects of new system of track facilities keeping are considered in the article.